Role of magnification and microscope in thyroid surgery safety and efficacy - K. S., Ravi; Naik, Kiran M.; M., Swarna Priya; M. P., Abhishek (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2021)
Background: Thyroid surgery becomes challenging, due to closely related structures like recurrent laryngeal nerve and parathyroid gland. Microscope assisted surgery has better visualization for dissection, and decreases the risk of injury to the nerve, parathyroid gland, and its vascular pedicle. Hence it decreases the operative complications. Methods: This is a retrospective study of microscope-assisted thyroidectomy at Adichunchanagiri hospital and research centre, from May 2016 to April 2020. Ethical approval was obtained from institutional review committee. Types of surgery, post-operative hypocalcemia and recurrent laryngeal nerve function were analysed descriptively. Results: Out of total 30 microscope assisted thyroidectomy, 26 were female, 42 (87.5%) benign pathology, 6 (12.5%) malignant. Hemithyroidectomy was done in 25 (83.3%), total thyroidectomy 4 (13.3%), and completion thyroidectomy with neck dissection in 1 (3.3%). Among total thyroidectomies, transient hypocalcemia occurred in 2 (6.6%) and no temporary or permanent recurrent laryngeal nerve palsy. Conclusions: The use of microsurgical technique and loupes magnification in thyroid surgery are safety and effective procedures that require an appropriate training in microsurgery, but may significantly reduce post-operative complications.